A comparison of Ukrainian and Hungarian school-leaving English exams - Huszti Ilona; Kacsur Annamária; Густі Ілона; Качур Аннамаріа; Annamaria Kachur (Видавничий дім «Гельветика», 2025)
Abstract. Annually, hundreds of millions of students worldwide face the crucial moment of their scholastic progression: matriculation examinations. These important assessments, often a critical gateway to tertiary education, influence future pathways of countless individuals. This is particularly true in Ukraine and its neighbouring country, Hungary, where these exams hold significant weight. In both nations, school-leavers undertake English matriculation exams at independent test centres ensuring impartiality and standardization. These centres operate under the watchful eyes of official government bodies, the Ministry of Education and Science in Ukraine and the Ministry of Human Resources in Hungary, guaranteeing adherence to national standards. In Ukraine, the English External Independent Evaluation (EIE) traditionally evaluated key reading, writing, and use of English skills. Notably, between 2018 and 2021 listening skills were also assessed. However, the onset of the devastating Russian-Ukrainian war on February 24, 2022 dramatically altered the academic environment. The 2022 English EIE was cancelled, replaced by the National Multi-disciplinary Test (NMT), which initially excluded English. In 2023, the NMT reintroduced an English component, featuring 32 items focused on reading comprehension and the use of English. On the other hand, a flexible two-tiered system for the matriculation exams is employed in Hungary: intermediate and advanced levels. Implemented since 2005, this structure provides a nuanced assessment of students' abilities. Both levels evaluate reading, listening, writing, and use of English skills, corresponding to B1 and B2 levels of the Common European Framework of Reference for Languages, respectively, in the written exam. Separate oral examinations assess speaking proficiency, ensuring a comprehensive evaluation. This article aims to compare and contrast the English matriculation examinations in these two Central European nations, highlighting the similarities and differences in their approaches to assessing English language proficiency.

Резюме. Щороку сотні мільйонів студентів у всьому світі стикаються з вирішальним моментом їхнього навчального процесу: випускними іспитами. Ці важливі оцінювання, часто критично важливий шлях до вищої освіти, впливають на майбутні шляхи незліченної кількості людей. Це особливо актуально для України та її сусідньої країни, Угорщини, де такі іспити мають значну вагу. В обох країнах випускники шкіл складають іспити з англійської мови в незалежних тестових центрах, що забезпечує неупередженість і стандартизацію. Ці центри працюють під пильним наглядом офіційних державних органів – Міністерства освіти і науки України та Міністерства людських ресурсів Угорщини, – гарантуючи дотримання національних стандартів. Описано, що в Україні зовнішнє незалежне оцінювання (ЗНО) з англійської мови традиційно оцінювало ключові навички читання, письма та використання англійської мови. Зокрема, у період з 2018 по 2021 рік також оцінювалися навички аудіювання. Однак початок руйнівної російсько-української війни 24 лютого 2022 року кардинально змінив академічне середовище. ЗНО з англійської мови 2022 року було скасовано, замінено Національним мультипредметним тестом (НМТ), який спочатку не включав англійську мову. У 2023 році НМТ знову запровадив компонент англійської мови, що містив 32 завдання, спрямовані на розуміння прочитаного та використання англійської мови. Охарактеризовано гнучку дворівневу систему випускних іспитів (середній і просунутий рівні), яка застосовується в Угорщині. Упроваджена з 2005 року, ця структура забезпечує детальну оцінку здібностей студентів. Обидва рівні оцінюють навички читання, аудіювання, письма та використання англійської мови, що відповідає рівням B1 та B2 Загальноєвропейських рекомендацій з мовної освіти, у письмовому іспиті. Окремі усні іспити оцінюють навички говоріння, забезпечуючи всебічну оцінку. Наша стаття має на меті порівняти та протиставити випускні іспити з англійської мови в цих двох центральноєвропейських країнах, висвітлюючи схожість та відмінності в їхніх підходах до оцінювання рівня володіння англійською мовою.
Порівняння українського та угорського випускних іспитів з англійської мови
Редколегія: https://nv.pdpu.edu.ua/Info/Index/05957923-0eae-4e75-90fe-1a179b3ff916 Зміст: https://nv.pdpu.edu.ua/Magazin
Keywords: advanced level; English school-leaving exam; External Independent Evaluation (EIE); Hungary; language skills; National Multi-subject Test (NMT); test; Ukraine; the Matura exam; поглиблений рівень; випускний іспит з англійської мови; зовнішнє незалежне оцінювання (ЗНО); Угорщина; знання мови; національний багатопредметний тест (NMT); випускний іспит в Угорщині; тест; Україна